2007
DOI: 10.1002/sia.2547
|View full text |Cite
|
Sign up to set email alerts
|

Bonding mechanisms of laser‐fabricated titanium/polyimide and titanium coated glass/polyimide microjoints

Abstract: In this study, two bimaterial joining systems, namely, titanium coated glass/polyimide (TiGPI) and titanium/polyimide (TiPI) are considered. The joints were prepared by employing transmission type laser-joining procedure. Both the TiGPI and TiPI bimaterial systems were subjected to tensile loading using a microtester, and failure loads per unit bond length were documented. The average failure strengths of the TiPI and TiGPI samples were found to be 5.1 and 7.3 N/mm, respectively. It is thus clear from the fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A number of studies by a group that assess transmission laser welding of thermoplastic polyimide to titanium coated glass for the purpose of microscale hermetic encapsulation are the only studies that investigate the key issues associated with polymeric enclosures, which include hermeticity and in vivo strength longevity [103][104][105][106][107][108][109]. Even though these studies do not assess complete polymer to polymer joining, they present important steps toward achieving this goal.…”
Section: Application Of Welding Methods For Polymer Based Encapsulationmentioning
confidence: 97%
“…A number of studies by a group that assess transmission laser welding of thermoplastic polyimide to titanium coated glass for the purpose of microscale hermetic encapsulation are the only studies that investigate the key issues associated with polymeric enclosures, which include hermeticity and in vivo strength longevity [103][104][105][106][107][108][109]. Even though these studies do not assess complete polymer to polymer joining, they present important steps toward achieving this goal.…”
Section: Application Of Welding Methods For Polymer Based Encapsulationmentioning
confidence: 97%
“…A transmission joining configuration1–10 was used in which, the joining material combination includes one absorbent and one transparent part at the laser wavelength. Laser energy penetrates the transparent part and is absorbed by the absorbing part, so that the heat is induced directly at the interface.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Our group has previously demonstrated that titanium and polyimide,2–6 and titanium‐coated glass and polyimide6–10 can be joined to form microbonds among bimaterials using lasers. The x‐ray photoelectron spectroscopy (XPS) results published in references1, 2 showed that titanium‐oxygen and titanium‐carbon chemical bonds are present at the laser joining interface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to the best knowledge of the authors, besides a few works carried out on the laser welding, the metal–polymer interfacial bond formation for welding‐based joining technologies has not been extensively explored. In Georgiev et al .…”
Section: Introductionmentioning
confidence: 99%